The Impact of Maternal Nutrition on Exclusive Breastfeeding Among Lactating Mothers - Meerab Ernest; Hajra Sarwar; Rohama Javed; Sehoon Javed; Anam Mushtaq (Journal of Health, Wellness and Community Research, 2025)
Background: Exclusive breastfeeding (EBF) during the first six months is critical for infant health, yet its success remains suboptimal in many regions, partly due to maternal nutritional deficiencies and limited awareness; existing evidence in Pakistan is sparse regarding the precise relationship between maternal diet and EBF adherence. Objective: This study aimed to evaluate the association between maternal nutritional status and exclusive breastfeeding practices among postpartum mothers, hypothesizing that adequate maternal nutrition is significantly linked to higher rates of exclusive breastfeeding. Methods: A cross-sectional observational design was utilized, recruiting postpartum mothers (n = 51) attending postnatal clinics at Ali Fatima Hospital, Lahore, from February to June 2025. Inclusion criteria comprised mothers aged ≥18 years, within six months postpartum, with singleton live births; those with chronic illnesses, severe postpartum complications, or infants with feeding-related anomalies were excluded. Data were collected through structured interviews and validated questionnaires assessing sociodemographic, dietary practices, and breastfeeding behaviors, complemented by anthropometric measures. Outcome measures included self-reported EBF adherence and dietary adequacy. Ethical approval was secured from the institutional review board in line with the Helsinki Declaration. Statistical analyses employed SPSS v27, with Chi-square and logistic regression used to explore associations and adjust for confounders. Results: Only 31.4% of mothers reported maintaining a balanced diet, and 31.4% practiced exclusive breastfeeding for six months. Adequate nutrition was significantly associated with higher EBF rates (62.5% vs. 17.1%; p = 0.001; OR = 4.31, 95% CI: 1.39–13.37), while knowledge and practice gaps persisted across educational strata. Conclusion: Maternal nutrition is strongly linked to exclusive breastfeeding, underscoring the need for integrated nutrition counseling and breastfeeding support within maternal healthcare. Prioritizing maternal dietary education can enhance breastfeeding outcomes and reduce preventable infant morbidity.